Study on Reutilization of Pyrolytic Residues of Oily Sludge. (23rd October 2020) - Tang, Chao; Guan, Jiaojiao; Xie, Shuixiang
Abstract : Pyrolytic residues of oily sludge are a kind of hazardous solid waste produced by high-temperature pyrolysis of oily sludge, which still contains a certain amount of mineral oil; improper disposal can cause secondary pollution. In order to reutilize the pyrolytic residues of oily sludge, the pyrolytic carbon in pyrolytic residues is recovered by a combination of physical flotation and chemical separation, and they are used for the treatment of oilfield wastewater and adsorption of oil. The results showed that the purity of the pyrolytic carbon is 95.93%; many pores of different sizes are distributed on the surface, with mainly mesoporous distribution. Specific surface area, pore volume, and average pore diameter reach 454.47 m 2 /g, 0.61 cm 3 /g, and 6.91 nm, respectively. Adsorption effect of pyrolytic carbon on COD and oil in oilfield wastewater is better than that of activated carbon at the same condition. With regard to adsorption on diesel and crude oil, the initial instantaneous adsorption rate of pyrolytic carbon is 3.8 times and 1.86 times faster than that of activated carbon, respectively. When pyrolytic carbon reaches saturated adsorption, cumulative adsorption of activated carbon on diesel and crude oil is much lower than that of pyrolytic carbon.